Cystic vein: a guide for safer laparoscopic cholecystectomy - Samal, Debasish; Sahoo, Rashmiranjan; Priyadarsini Mishra, Sujata; B. Maiti, Krishnendu; Patra, Kalpita; Chandra Sahu, Mahesh (International Surgery Journal, 2017)
Background: Major complications of laparoscopic cholecystectomy are bleeding and bile duct injury, and it is necessary to clearly identify structures endoscopically to keep bleeding and injury from occurring. The aim of this study was to depict the anatomic landmark in the Calots triangle, a vein (cystic vein), a constant feature which can help Laparoscopic surgeons to conduct a safe LC along with other precautions to be adopted. Methods: A total of 100 patients (58 male, 42 female) who underwent cholecystectomy were examined preoperatively by clinically. The origin and number of cystic veins and their relationship with the Calot triangle was evaluated. Results: The cystic veins were delineated intraoperatively in 80 of the 93 patients. The relationship between the cystic vein and the Calot triangle was identified in 80 (86.02%) of the 93 patients. One cystic vein was found in 53 (66.25%) patients, while multiple cystic veins were found in 27 (33.75%) patients. All these veins are above the cystic common bile duct junction. Conclusion: The configuration of the cystic veins and their relationship in the Calot triangle with cystic artery and cystic duct can be identified intraoperatively and used as a guideline for safe laparoscopic cholecystectomy.